The Problem of Artifacts in Saint Petersburg’s Architecture in the Second Quarter of the 19th Century - Mikishat’ev, Mihail N. (Actual Problems of Theory and History of Art, 2018)
In the present article the problem of artifact in architecture is examined as a phenomenon of inclusion of the original or reproduced object from another era or another culture in composition of an architectural work of the Modern period. The problem of artifact in architecture of the Modern period arose in the second half of the 18th century due to real acquaintance of the European culture to heritage of antiquity and the culture of the ancient East. However till the 19th century stylization predominated. In the 30s of the 19th century in St. Petersburg architecture an important period in the development of the European art and world outlook finished. The century of eclecticism began. And its first phase passed under the sign of “historicism” or “an archaeological method”. Masters of historicism entered antique prototypes into the composition of their works, trying to reproduce them with maximum accuracy. The “artifact” included in composition often was opposed to the general character of a construction. In the second half of the 19th century the eclectic method followed a way of free mixture and configuration of elements of different historical styles. Imaginary artifacts gave way to the museum pieces which were located in interiors again as was in the 18th century.